Effects of non-equidistant rates of N, P and K on leaf concentrations of these nutrients and on yield of corn (Zea mays L.) - Neptune, Andre Martin Louis; Nakagawa, Julio; Scotton, Luiz Carlos; Souza, Euclides A. de (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1982)
The experiments here in described were carried out in a podzolic soil, in the Sate of São Paulo, Brazil, with the double hybrid corn HD-6999 B. The aim of the work reported in this paper is to determine the critical N, P, K levels or percentages associated with the fertilizer rates that give the maximum yield and the maximum profit. To arrive at a critical nitrogen, phosphorus and potassium economical level in the corn leaf, it was calculated the maximum economical yield attainable under the conditions presented in this study by using the Mitscherlich and Pimentel Gomes and Malavolta equation. The foolowing results have been found: Rates of fertilizers (kg/ha): 228(N), 80(P2O5), 50(K2O) - 100(N), 253(P2O5), 50(K2O) - 100(N), 80(P205),61,7(K2O); Maximum economical corn yield (kg/ha): 11,000 - 6,877 - 9,252; Critical nutrients level: 3,27% N - 0,293% P - 2,07% K